2018
DOI: 10.30880/jst.2018.10.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light Intensity on the Photosynthesis and Phenolic Contents of Mangifera Indica

Abstract: Light is an important environmental factor that have an influence on a plants photosynthesis and production of secondary metabolites like phenolic compounds and flavonoid. Mangifera indica from the family Anacardiaceae is known to have bioactivity due to its phenolic and flavonoid contents. The objective of the study is to determine the influence of light on the photosynthesis and phenolic contents of M. indica. Photosynthesis of the plant was measured using a portable photosynthesis system referred to as LICO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(46 reference statements)
1
6
0
1
Order By: Relevance
“…Linatoc et al . ( 34 ) reported that M. indica leaves exposed to the sun accumulated higher amounts of phenolic compounds than the shaded ones.…”
Section: Resultsmentioning
confidence: 99%
“…Linatoc et al . ( 34 ) reported that M. indica leaves exposed to the sun accumulated higher amounts of phenolic compounds than the shaded ones.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated an increase in the production of phenolic acids and flavonoids following high light exposure. In this case, no stress was applied to the plants; however, leaves are naturally more exposed to light as compared to roots [ 38 ]. This can explain the presence of a higher number of phenolic compounds in leaves compared to roots.…”
Section: Discussionmentioning
confidence: 99%
“…This normalized SPD is multiplied with the conversion factor F to obtain the simulated SPD [24] using " (13)," Φe,v = Φ(𝝺,𝞓𝝺0.5,𝝺o) * F (13) where F represents the ratio of total radiant power or luminous flux or PPF and integral of the normalized spectrum [23]. If the PPF is known, F can be calculated using " (14)," 𝐹 = 𝛷 𝑝 8.359 * 10 −3 * ∑ 𝜆 * 𝛷(𝜆,𝛥𝜆 0.5 ,𝜆 0 ) * 𝛥𝜆 700 𝑘=400 (14) If only the total radiant power is known, F can be calculated using " (15)," 𝐹 = 𝛷 𝑒 ∫ 𝛷(𝜆,𝛥𝜆 0.5 ,𝜆 0 ) * 𝑑𝜆 (15) If only the luminous flux is known, F can be calculated [24] using " (16)," 𝐹 = 𝛷 𝑣 𝑘 ∫ 𝛷(𝜆,𝛥𝜆 0.5 ,𝜆 0 ) * 𝑉(𝜆) * 𝑑𝜆 (16) Initially, the SPD of the LED light source was considered as the target spectrum. For mimicking the target spectrum, the selection of optimal LEDs is required.…”
Section: Led Modellingmentioning
confidence: 99%
“…Plant phenolic content, considered the best natural antioxidant to prevent several illnesses such as cancer, diabetes, inflammatory problems [8]. Phenolic compounds are synthesized by plants to survive stress conditions and play a vital role in accumulating phenolic compounds [15], [16].…”
Section: Introductionmentioning
confidence: 99%